Family Support in Controlling Hypertension among the Elderly in Lhokseumawe City: A Descriptive Phenomenological Study (International Journal of Nursing Education, 2022)
Family is the main support system in caring for its members, including the elderly with hypertension. Treatment of the disease in old people is through help from a spouse, child, or close relatives because they often live with their families. Therefore, this study aims to determine the form of family support in controlling hypertension among the elderly, including physiological, psychological, socio-cultural, and spiritual supports. The qualitative method was used with a descriptive phenomenological approach. The respondents consist of eight family members who cared for the elderly with uncomplicated hypertension during the past year. The themes found include responding to hypertension with traditional ingredients, the existence of quality time with the elderly, being free to select the activities they like, and prioritizing themselves to worship a lot. Based on the results, efforts are needed from community nurses to provide health promotion education on the importance of family support in controlling hypertension amond people.
Keywords: Elderly, Family Support, Hypertension Control